Changing attitudes of high school students in Israel toward homosexuality. Issue 1 (2nd April 2016) - Eick, Uri; Rubinstein, Tanya; Hertz, Shai; Slater, Aylon
ABSTRACT: Hoshen, the Hebrew acronym for "Education & Change", is a nonprofit, nationwide education and information center for the lesbian, gay, bisexual, and transgender (LGBT) community in Israel. The main educational method Hoshen uses is the personal story told by volunteers. The present study aimed to examine whether this activity, carried out in Israeli high schools, resulted in a change in participants' attitudes. Questionnaires measuring Attitudes Towards Homosexuality were administered to 272 students in 3 high schools before and after the activity. Results showed an improvement in the general Attitudes Towards Homosexuality scale, and in all three subscales of the attitudes towards homosexuality construct measured in this study: emotional, cognitive and behavioral. A very significant impact was observed on the emotional subscale. Young men showed a sharper rise in acceptance of homosexuality than did women. Religiosity, form of residence (urban vs. nonurban), and previous acquaintance with LGBT people showed to also have an effect on attitudes. Results of this study indicate that the personal story method is effective in changing attitudes toward homosexuality. This change might help create a safer environment for LGBT teens. Social change organizations may be able to use this method to promote tolerance towards other minorities as well.